Analisis Keikutsertaan Wanita Usia Subur Dalam Upaya Deteksi Kanker Serviks Di Puskesmas Binong Kabupaten Tangerang Tahun 2022: Analysis of the Participation of Women of Reproductive Age in the Efforts to Detect Cervical Cancer at the Binong Health Center, Tangerang Regency - Widiyaningrum, Erlina (Dohara POAJ, 2023)
Introduction: Cervical cancer is the fourth type of cancer that most often affects women. One of the prevention efforts is by using the IVA test method. The results of a preliminary study at the Binong Health Center, Tangerang Regency, only 29 women took the IVA Test, and 5 of them were detected positive. The purpose of writing was to analyze the participation of women of childbearing age in efforts to detect cervical cancer at the Binong Health Center, Tangerang Regency, in 2022. Methods: This research is quantitative-analytic research with a cross-sectional approach. The sample was WUS aged 25-45 years who were married in the working area of ​​the Binong Health Center, Tangerang Regency, with a total of 335 people using a purposive sampling technique. The variables in this study were IVA test participation, knowledge, attitudes, sources of information, and husband's support. Bivariate analysis using the Chi-Square test. Results: The results of the univariate study 60,0% of WUS did not carry out an IVA test. The results of the bivariate study showed that there was a relationship between knowledge (p=0.000, OR=18.632), attitude (p = 0,000; OR=3,299); sources of information (p=0,000; OR=5,331); and husband's support (p = 0,000; OR = 2,621). Discussion: Knowledge has a high probability of WUS participating in the IVA test. It is hoped that health workers can help increase knowledge and motivate WUS in carrying out early detection of cervical cancer, especially with the IVA test method through providing information during examinations, by placing posters or distributing leaflets so that WUS understand and can remember when they forget.